Efficacy of a local-drug delivery gel containing extracts of Quercus brantii and Coriandrum sativum as an adjunct to scaling and root planing in moderate chronic periodontitis patients - Jaber Yaghini; Mohammad Shahabooei; Abolfazl Aslani; Mozhgan Reza Zadeh; Sima Kiani; Narges Naghsh (Wolters Kluwer Medknow Publications, 2014)
Objective: Recent advances in the field of alternative medicine introduced various herbal products for the treatment of periodontitis. The purpose of this study was to evaluate the effects of combined extracts from Quercus brantii and Coriandrum sativum on periodontal indices in adult periodontitis patients. Methods: In this randomized, double-blinded clinical trial, performed in Isfahan Dental School in 2012, a new herbal medicament containing combined extracts from Q. brantii and C. sativum was formulated in the gel form for subgingival application. Following scaling and root planing (SRP), both herbal and placebo gels were delivered at the experimental and control sites, respectively. Periodontal pocket depth, clinical attachment level, papilla bleeding index, and plaque index were measured at baseline, 1 month and 3 months later. Both intra-and inter-groups changes were registered. The obtained data were analyzed by SPSS software, using repeated measure analysis of variance, paired t-test, Mann-Whitney, Friedman, and Wilcoxon tests. Differences with P < 0.05 were considered to be significant. Findings: Both groups indicated statistically significant improvements in the periodontal indices (P < 0.05), but there were no significant differences between two study groups with this regard. Conclusion: The herbal gel does not have considerable advantages over SRP alone as an adjunct in periodontal treatment.